2022
DOI: 10.3389/fimmu.2022.873947
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Can Induce CD4-Mediated Responses to Homocitrullinated Peptides via Multiple HLA-Types and Confer Anti-Tumor Immunity

Abstract: Homocitrullination is the post translation modification (PTM) of the amino acid lysine to homocitrulline also referred to as carbamylation. This PTM has mainly been studied in relation to autoimmune diseases including rheumatoid arthritis. Homocitrullination of lysines alters their charge which can lead to generation of neoepitopes that are differentially presented by MHC-II and induce modification-specific immune responses. Homocitrullination is often considered a process which triggers autoimmune disease by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 57 publications
4
11
0
Order By: Relevance
“…However, responses vary between different mice strains. These results also support previous data (5,10) and confirm that responses to the Modi-2 peptides are homocitrullinespecific and mediated by CD4 T cells.…”
Section: Responses To Homocitrullinated Peptides Can Be Stimulated In...supporting
confidence: 92%
See 3 more Smart Citations
“…However, responses vary between different mice strains. These results also support previous data (5,10) and confirm that responses to the Modi-2 peptides are homocitrullinespecific and mediated by CD4 T cells.…”
Section: Responses To Homocitrullinated Peptides Can Be Stimulated In...supporting
confidence: 92%
“…We have previously shown that homocitrullinated (Hcit) peptides derived from aldolase A (Aldo), immunoglobulin heavy chain-binding protein (BiP), cytokeratin 8 (Cyk8) and vimentin (Vim) can stimulate CD4 T cell responses through multiple MHCII alleles in standard and HLA transgenic mice including HLA-HHDII/DR1, HLA-HHDII/DP4, HLA-DR4 and Balb/c mice. We have also observed that among several peptides screened, Aldo74-93 Hcit , BiP562-579 Hcit , Cyk8 371-388 Hcit and Vim116-135 Hcit peptides induced T cell responses in the different mouse strains mentioned above (5,10). These epitopes are homologous in humans and mice.…”
Section: Responses To Homocitrullinated Peptides Can Be Stimulated In...mentioning
confidence: 63%
See 2 more Smart Citations
“…However, if citrullination is a normal stress response, it cannot be restricted to only HLA‐DR4 +ve and HLA‐DR1 +ve individuals. We, and others, have previously demonstrated that citrullinated peptides can bind to both HLA‐DP4 [16] and HLA‐DQ alleles [17] implying a wider HLA presentation profile for citrullinated and homocitrullinated peptides [18, 19].…”
Section: Introductionmentioning
confidence: 99%